2009
DOI: 10.1111/j.1365-2982.2009.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Fall in density, but not number of myenteric neurons and circular muscle nerve fibres in guinea‐pig colon with ageing

Abstract: In guinea-pig ileum, ageing has been associated with a decrease in enteric neurons. This study examined guinea-pig colon and measured changes in gut dimensions, neuron size, density and ganglionic area. Changes in motor nerve fibres in the circular muscle were also measured. Myenteric neurons in whole-mount preparations of mid-colon from 2-week, 6-month, and 2-year-old guinea-pigs were labelled immunohistochemically with the neuronal marker human neuronal protein HuC/HuD, and numbers of neurons mm(-2), neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 38 publications
7
47
0
4
Order By: Relevance
“…Similar results were observed in the guinea pig small intestine [13], the stomach of sheep [26], and a mouse [9]. However, some recent research has shown that there is no significant loss in the number of neurons in the myenteric plexus associated with aging [14,24,36]. We assume that the reasons for these differences may be due to technical difficulties in the precise counting of the number of neurons.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar results were observed in the guinea pig small intestine [13], the stomach of sheep [26], and a mouse [9]. However, some recent research has shown that there is no significant loss in the number of neurons in the myenteric plexus associated with aging [14,24,36]. We assume that the reasons for these differences may be due to technical difficulties in the precise counting of the number of neurons.…”
Section: Discussionsupporting
confidence: 61%
“…These studies were carried out in a number of animal species [27,29,31]. The literature that has been documented support varying data from those which indicate the significant reduction (30-50%) in the number of neurons [17,33] to those where there is no significant loss of the neurons [14,24,36] in the aging process. There are a number of studies [7,34] which describe changes in ENS due to the introduction of certain dietary restrictions in experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, others have shown that the expression of neuronal nitric oxide synthase (nNOS) is differentially affected in young and aged rats [7]. Preclinical studies in the guinea pig colon have also shown that aging has been associated with a decrease in neurons in the ENS; however, a fall in density rather than the number of myenteric neurons is thought to be the major change with age [8]. Although data from humans to investigate age-related changes in the colon are limited, recent evidence from human sigmoid colon circular muscle suggests that a decrease in nerve fiber density occurs with growth in response to an increase in circular muscle thickness that occurs during early childhood to adolescence; however, this study found no further changes were observed with aging [9].…”
Section: Enteric Innervationmentioning
confidence: 95%
“…They also show impaired colonic transit and constipation [18]. For example, in the intestine of aged guinea-pigs, there is a reduction of approximately half the number of myenteric neurons in the small intestine, with no reduction in the neuronal cell size [19]. Also, in rats, there is a clear reduction in the number of myenteric neurons, which has been directly associated with a reduction in output of fecal pellets with age [18].…”
Section: Loss Of Enteric Neurons and Interstitial Cells Of Cajal In Hmentioning
confidence: 97%